The Use of Modern Technologies in the Development of Mathematical Knowledge of Preschoolers (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
the article discusses the use of modern technologies in the development of mathematical knowledge of preschoolers, the importance of a problematic situation in the learning process, and suggests types of entertaining games for the development of thinking and mathematical knowledge of preschool children.